The Cauchy-Stieltjes integrals in the theory of analytic functions - Ryazanov, V.I. (Український математичний вісник, 2017)
We study various Stieltjes integrals as Poisson–Stieltjes, conjugate Poisson–Stieltjes, Schwartz–Stieltjes and Cauchy–Stieltjes and prove theorems on the existence of their finite angular limits a.e. in terms of the Hilbert–Stieltjes integral. These results hold for arbitrary bounded integrands that are differentiable a.e. and, in particular, for integrands of the class CBV (countably bounded variation).